Track access charges in the European Union railroad sector: A consideration of company organization and institutional quality - Andreas Schöne; Philipp Kunz-Kaltenhäuser (Technische Universität Ilmenau, Institut für Volkswirtschaftslehre, 2022)
Track access charges are the main driver of infrastructure costs for rail operators in the rail transport sector, accounting for up to 88 percent of costs. This paper analyzes track access charges of 28 EU countries with the respective trajectories of the company forms employing panel regressions to unbalanced panel data for the period 2011 to 2019. As a result, a fundamental correlation between company forms and track access charges could be determined. Starting from a vertically integrated company, massive cost advantages could be identified for unbundled and partially privatized company forms by avoiding efficiency-impeding behavior. The results shed light on the European railroad packages and their national implementation.
Keywords: L11; L14; L42; L51; L52; 330; Track Access Charges; Railroad Sector; Institutional Quality; Transportation; Industrial Policy